Studi deskriptif pelaksanaan ekstrakurikuler pendidikan kepramukaan di SD Negeri 72 Bengkulu Tengah - Putri Awdiani, Dhea; Lukman; Nady Febri Ariffiando (JURIDIKDAS, 2024)
This research aimed to describe the implementation of scout education extracurricular at State Elementary School 72 Central Bengkulu. This research was qualitative research using descriptive approach. The subjects in this research were the principal, homeroom teacher, scoutmaster, and students. The instruments used in this research were observation guideline, interview, questionnaire, and documentation. The technique of data processing used in this research was milles and huberman data analysis technique consisted of data collection, data display, data reductions, and drawing conclusion/verification. The results showed that the implementation of scout education extracurricular at State Elementary School 72 Central Bengkulu was carried out in two models namely block model and regular model, while for the actualization model for scout education was not conducted yet. The implementation of scout education extracurricular block model and regular model implemented at State Elementary School 72 Bengkulu was implemented in line with the guideline of scout education implementation obtained in the regulation of minister of education number 63 year 2014 started from the stage of planning, process, and assessment. While for the implementation of scout education extracurricular actualization model was not implemented yet in accordance with the regulation of minister of education number 63 year 2014, thus based on the research results it could be concluded that the implementation of scout education extracurricular at State Elementary School 72 Central Bengkulu is not yet in accordance with curriculum 2013 because it does not apply thoroughly the scout education model as stated in curriculum 2013.